P-411 Blood concentrations of specific (PCBs) congeners and abortion rates in healthy women undergoing IVF cycles living in areas with high and low pollution. (EcoFoodFertility Project). (30th June 2022) - Montano, L; Gentile, R; Gentile, M; Gentile, T; Spinelli, M; Carolina, F; Notari, T; Piscopo, M; Amoresano, A; Raimondo, S
Abstract: Study question: Human exposure to polychlorinated biphenyls (PCBs) exists despite its ceased production since 1977. PCBs congeners harm reproductive health, but data remain inconclusive. Summary answer: Evaluate relationship between blood concentrations of specific (PCBs) congeners and abortion rates in women undergoing IVF cycles living in areas with high and low pollution. What is known already: PCBs are a class of synthetic chemicals that were widely used in industry until the 1970s and are found in many consumer products as refrigerants in electrical equipment, as flame retardants in plastics production and electronics. Continuous exposure to PCBs is of concern because they fall into the group of endocrine disruptors (EDCs), PCB congeners can spread throughout the female reproductive tract. Indeed, they have been found in human follicle fluids, placenta, amniotic fluid in embryos and fetuses Despite multiple reproductive health effects in women was reported, the results are sometimes inconsistent between experimental and epidemiological studies. Study design, size, duration: In the frame of EcoFoodFertility Project, a cross sectional study conducted in Campania Region (Italy) to assess environmental impact on fertility and human health, blood samples were collected during the IVF cycles of the 65 women (aged 27.8 + 3.6) no smokers, BMI 23.5 – 27.9, normal menstruation, in two areas with high and low pollution between 2017 and 2019. The PCBs congeners we investigated were: estrogenic congeners (31, 44, 52, 101, 153), anti-estrogenic congeners (77, 105, 110, 114, 126, 156, 169) and other (28, 118, 138, 180). Participants/materials, setting, methods: Group A (n = 30) living in low polluted area (LPA), alto Medio Sele in province of Salerno, and group B (n = 35) living in highly polluted area (HPA), known as the "Land of Fires" due to the many sources of pollution. The blood sample was taken on the day of the oocyte pick-up and PCBs were measured by Gas Chromatography Coupled to (tandem) Mass Spectrometry. Statistical analyses were performed by GraphPad Prism 9. Main results and the role of chance: Blood concentrations of PCBs are expressed as wet weight (nanograms per gram of serum) and as standardised lipid concentrations (nanograms per gram lipid). The PCB 169 congener was found in the highest concentration, 229.62 ng/g and, on average, accounted for 46.2 % of ΣPCBs tested. The PCB 77 (p < 0.05) and 118 ((p < 0.001) congeners were significantly higher in participants permanently living in HPA (Group B). For the other congeners, no significant variation was found. No significant variations between the two groups for oocyte pick-up rate, metaphase I and II oocyte ratio was found, fertilisation rate and pregnancy rate. Furthermore, the probability of embryo implantation was similar between the two groups, but the abortion rate was 3.0 times higher in group B. The probability of live births is 85.7% in group A and 53.85% in group B.These findings, even if the results between PCBs exposure and reproductive outcomes are due to the different congeners of these chemical compounds and unknown confounding factors and exposure times may be implicated, however suggest an association between the detection of specific PCB congeners and increased abortion rates in women undergoing IVF cycles that cannot be understimated. Limitations, reasons for caution: Although we have set up a strict control and survey protocol, our study also has limitations due to the relatively small sample size of the groups and as with almost all epidemiological studies on environmental impact, there may be confounders or co-exposures that could interfere with the observed associations. Wider implications of the findings: Although PCBs are no longer produced, the exposure remains widespread due to their long biological half-life, accumulation in the food chain and human health impacts are still reported. Our findings confirm these concerns, therefore, the study of these old chemicals is still relevant and important and should be expanded. Trial registration number: not applicable